DINAMIKA KONFLIK ANTAR STAKEHOLDER PADA IMPLEMENTASI KEBIJAKAN PENGOLAHAN DAN PEMURNIAN MINERAL DALAM NEGERI DI PROVINSI LAMPUNG - Rina Herlina Haryanti, Shinta Mardiana Dewi, Ismi Dwi Astuti Nurhaeni & (Master of Public Administration, Universitas Slamet Riyadi, 2018)
The purpose of the research is the research is menganalisisdinamikaconflicts between stakeholders on the implementation of the policyprocessing and refining of minerals in the country in the province ofLampung. This research is descriptive research using the analysis of thecontents of documents and interactive analysis. Primary data come fromin purposive sampling techniques with informants from the Department ofmines and energy, entrepreneurs, workers, society. Research datacollected through interview techniques, documentation, and observations.The next step using triangulation data source to gaThe validity of thedata. The results showed the existence of conflicts betweenstakeholders to create a policy this is not teraplikasi in the province ofLampung. The process of the conflict at the stage of interpretation aredominated by the conflict discourse at the central; organizing stage,marked by conflicts between the implementing policies; Stage of theapplication, with regard to the conflict between local entrepreneurs withthird parties arising due to the suspension of the company. Factors whichaspects influenced the conflict include differences between stakeholderNeeds; the less effective communication; Emotional tension with peaks onthe filing of a judicial review; The difference in value; strukturdengan theexistence of suppressor groups; The history of past management andforeign investment. The type of conflict by subject is interpersonal conflictbetween the Governments, local entrepreneurs, a third party. Substancesare realistic conflict, with reserves of the deposit, high investment andinfrastructure facilities that do not support the output of the constructivenature of the conflict, with the presence of negotiation and it embodied inthe form of a revision of policy. According to the areas of life, the conflict isa conflict of ekonomidan politics, namely the scramble for mineralresources by using the power and authority.Key words: conflict, stakeholders, policy processing and refining of minerals